Practice Patterns and Utilization of Tube Feedings in Acute Pancreatitis Patients at a Large US Referral Center. Issue 9 (October 2018) - Machicado, Jorge D.; Gougol, Amir; Paragomi, Pedram; O'Keefe, Stephen J.; Lee, Kenneth; Slivka, Adam; Whitcomb, David C.; Yadav, Dhiraj; Papachristou, Georgios I.
Abstract : Objectives: Clinical trials on tube feedings (TFs) have not been sufficiently powered to change practice patterns in acute pancreatitis (AP). We aimed to describe the use, duration, and resource utilization of TF in AP patients at an expert US center. Methods: Of 423 AP patients prospectively enrolled at the University of Pittsburgh Medical Center from 2004 to 2014, 139 (33%) received TF. Data on TF were assessed in 100 (72%) of 139 patients with complete data available. Results: Patients on TF were more likely to be male, be obese, have alcohol etiology, and have moderately severe (34% vs 19%) or severe AP (62% vs. 3%) ( P < 0.05). Tube feedings were started after a median of 5 days (interquartile range, 3–8 days) from admission and were administered for a median of 39 days (interquartile range, 19–58 days). A nasojejunal route (95%) with an oligomeric formula (92%) was the preferred TF strategy. Feeding tube complications led to at least 1 endoscopic tube replacement in 42% of patients and to an unexpected health care visit in 29% of those discharged on TF (16/55 patients). Conclusions: Tube feedings form an important component in the management of patients with moderately severe and severe AP. Further studies should define the optimal utilization of TF and ways to reduce TF-related complications. Abstract : Supplemental digital content is available in the text.